Antitumor effects of anlotinib in thyroid cancer. Issue 1 (January 2019) - Ruan, Xianhui; Shi, Xianle; Dong, Qiman; Yu, Yang; Hou, Xiukun; Song, Xinhao; Wei, Xi; Chen, Lingyi; Gao, Ming
Abstract : There is no effective treatment for patients with poorly differentiated papillary thyroid cancer or anaplastic thyroid cancer (ATC). Anlotinib, a multi-kinase inhibitor, has already shown antitumor effects in various types of carcinoma in a phase I clinical trial. In this study, we aimed to better understand the effect and efficacy of anlotinib against thyroid carcinoma cells in vitro and in vivo . We found that anlotinib inhibits the cell viability of papillary thyroid cancer and ATC cell lines, likely due to abnormal spindle assembly, G2/M arrest, and activation of TP53 upon anlotinib treatment. Moreover, anlotinib suppresses the migration of thyroid cancer cells in vitro and the growth of xenograft thyroid tumors in mice. Our data demonstrate that anlotinib has significant anticancer activity in thyroid cancer, and potentially offers an effective therapeutic strategy for patients of advanced thyroid cancer type.